Cycloartane-Type Saponins, Phytochemical-Rich Extracts, and Sub-Extracts from Astragalus noeanus Boiss. Exhibit In Vitro and In Silico Effects on Glucose Metabolism - Ozdemir-Baycinar, Kevser; Barak, Timur Hakan; Kurt-Celep, Inci; Ozbek, M. Olus; Wang, Dongdong; Savasan, Ozan; Eroglu Ozkan, Esra (Mdpi, 2026)
Background/Objectives: This study aimed to evaluate the antidiabetic potential of five extracts/sub-extracts and five known cycloartane saponins [astragalosides (AST) I, II, III, IV, and cyclocanthoside E] from Astragalus noeanus (AN), using four specific diabetes-related molecular targets. Methods: Four diabetes-associated in vitro and in silico targets-protein tyrosine phosphatase 1B (PTP1B), dipeptidyl peptidase IV (DPP IV), alpha-amylase, and advanced glycation end-products (AGEs)-were employed to obtain comprehensive antidiabetic activity profiles. Additionally, the antioxidant and prebiotic capacities of the extracts/sub-extracts were assessed in vitro. A cycloartane saponin was isolated and structurally characterized. Quantitative analyses of total flavonoids, total saponins, and high-performance thin-layer chromatography (HPTLC) were performed to profile the chemical constituents of the plant material. Results: Among the extracts/sub-extracts, the aqueous extract (ANW) exhibited the highest inhibitory effects against all four diabetes-related targets, with inhibition percentages ranging from 83.70% to 93.49%. The methanol extract (ANM) demonstrated significant prebiotic activity comparable to standard controls on two Lactobacillus strains. The chloroform extract (ANC) showed the highest flavonoid content and exhibited the strongest antioxidant activity across all assays. ANM yielded the highest saponin content (3250 mg escin equivalent/g). HPTLC quantification revealed that AST IV was the predominant saponin in ANM (14.28 mu g/mg) after cyclocanthoside E (117.27 +/- 6.71 mu g/mg). Among the saponins, AST IV displayed the most potent inhibition in diabetes-related enzyme assays, surpassing reference drugs acarbose and vildagliptin at equivalent concentrations. AST III also demonstrated considerable activity, ranking just below AST IV. Molecular docking studies identified AST II and AST III as the most promising ligands, exhibiting superior binding affinities and stronger hydrogen bonding and hydrophobic interactions with target proteins. Cyclocanthoside E was isolated from A. noeanus and evaluated for its antidiabetic effects for the first time, with its structure confirmed by NMR and LC-HRMS analyses. Conclusions: This study highlights Astragalus noeanus as a promising source for safe and effective antidiabetic agents. The potent activity of the aqueous extract, along with AST IV and AST III, warrants further investigation through clinical trials to validate their therapeutic potential in diabetes management.
Keywords: Astragalus noeanus; antidiabetic activity; alpha-amylase; DPP IV; PTP1B; AGEs; prebiotic; antioxidant activity; molecular docking